To be, or not to be - a punk; Identity construction within Punk subculture - Ljevar, Vanja (2014)
The purpose of this research was to explore punk identity. The previous work provided lenses through which we can observe punk identity as being a dynamic construct, sculpted by the processes of differentiation and assimilation. Another significant concept in terms of this investigation was authenticity, as the ultimate form of punk identity and constituent features that are supposed to be the bases of the identity. Each of these concepts were explored using interpretative repertoires that were recognized as linguistic patterns in the speech of participants. In contrast to the literature, this study shows how punks do not only use the dynamic, anti – essentialist idea of identity, they also have the quite stable idea of identity that changes in regard to different topics. Therefore, the aim of this research was to denote when and why these repertoires were used and how they enhance one’s sense of self.